Modification and expansion of a computer aided design package for process flowsheet development - Dizdaroğlu, Gülseda. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 1986., 1986)
An interactive design calculation package (DESPAC), prepared under the direction of Prof. A. Westerberg at Carnegie-Mellon University, contains flash, disti'llation and absorption routines. In this study DESPAC was firstly modified from the DEC-20 computer system to the CDC Cyber 170/815 computer system and then expanded by adding the multicomponent liquid-liquid extraction and the shell-and-tube heat exchanger computation modules. The new package (DESPAC2) is capable of solving steady-state problems for various process flowsheets on a unit by unit basis. DESPAC2 has a library file which comprises some thermophysical properties for ninety-one chemical species. This file can be extended defining new properties and components. In addition to this, it is possible to introduce new unit computations into DESPAC2. The methodology required for this purpose, is explained in detail. In order to present the flexibility of DESPAC2, various examples are solved. Firstly six problems involving single operation units are studied. Secondly various flowsheets are proposed and tested for a separation problem as an example of flowsheet development using DESPAC2. This package is simple to use and can be employed for wide range of applications including flowsheet development, process design, in research and education.
Keywords: Distillation.; Absorption.